1979
DOI: 10.1071/bi9790587
|View full text |Cite
|
Sign up to set email alerts
|

Control of Parturition in the Sow Using Progesterone and Prostaglandin

Abstract: The effect of progesterone and prostaglandin administration on the timing of farrowing was studied in three groups of 25 sows each .. Progesterone treatment (100 mg/day) on days 112, 113 and 114 of gestation (group I) significantly prolonged the gestation length to 116 A±0·4 (mean±s.e.) days compared to the control sows (group III; 115·5 ±O· 2; P < 0 ·05). Administration of prostaglandin (200 I1g Cloprostanol intramuscularly) on day 115 of gestation following progesterone treatment (group II) resulted in a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…Despite a decrease following parturition, our data confirm that plasma PRL concentrations remain relatively high thereafter, which is likely due to stimulation by the suckling piglets [36,37]. The existence of a negative correlation between P4 and E2 and, between P4 and PRL, together with the coincidental fall of P4 on the one hand and rises in E2 and PRL on the other hand, support the proposed role of the P4 decrease as the trigger for other hormonal variations at parturition [3,4,35,38].…”
Section: Plasma Hormones Lactose and Igg Variations Around Parturitionsupporting
confidence: 75%
“…Despite a decrease following parturition, our data confirm that plasma PRL concentrations remain relatively high thereafter, which is likely due to stimulation by the suckling piglets [36,37]. The existence of a negative correlation between P4 and E2 and, between P4 and PRL, together with the coincidental fall of P4 on the one hand and rises in E2 and PRL on the other hand, support the proposed role of the P4 decrease as the trigger for other hormonal variations at parturition [3,4,35,38].…”
Section: Plasma Hormones Lactose and Igg Variations Around Parturitionsupporting
confidence: 75%
“…Although the accumulation of lactose in the mammary tissue of the rat is a convenient method of determining the initiation of lactose synthesis, it is not possible to use this criterion in larger species. Therefore, in studies in cows (Hartmann 1973), ewes , women (Kulski et al 1977(Kulski et al , 1978 and sows (Gooneratne et al 1979), the initiation oflactose synthesis during lactogenesis has been determined by changes in the concentration of lactose in the mammary secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Another study shown that prolonging the gestation to 116 days using i.m. injections of P4 did not signifi cantly affect litter sizes at birth and at 19 days after farrowing (GOONERATNE et al, 1979). The average number of piglets born reported in that study was around 9, which represents about 5 piglets less than the average obtained with high prolifi c sows in the current study.…”
Section: Discussionmentioning
confidence: 62%
“…Previous experiments demonstrated that sows fed MPA in the last days of gestation underwent spontaneous luteolysis and the endogenous progesterone levels decreased during the treatment period at the same time that in control animals (WHITELY et al, 1990). Similarly, it was demonstrated that exogenous progesterone supplementation between days 112 and 114 of gestation induced corpora lutea regression (GOONERATNE et al, 1979).…”
Section: Discussionmentioning
confidence: 90%